(untitled) (Research, Society and Development, 2022)
Maternal mortality is an important indicator that reflects public health problems, as well as conditions of determinants and conditioning factors in health. With the advent of the pandemic of COVID-19, vulnerable populations and individuals became susceptible to the disease, among them pregnant women, who became a group of great concern, given the evolution of maternal death at extremely high levels associated with COVID-19. In this sense, this study aims to identify the risk factors associated with maternal mortality during the pandemic of COVID-19. This is a cross-sectional study, with a descriptive approach, of the integrative literature review (ILR) type. For data collection strategy, the bibliographic databases were used: PubMed, LILACS and SciELO, using inclusion and exclusion criteria to select the publications. The results showed that several factors can influence maternal mortality, some directly and others indirectly. The signs and symptoms of COVID-19 were an important predictor for the most severe cases, besides being strongly associated with those pregnant women who have some comorbidity, who needed hospitalization or even mechanical ventilation, as well as age, pregnant women from low and middle income countries, among other characteristics linked to maternal mortality. In this sense, it is concluded that there is a need for more attention to the health conditions of pregnant women, both in the sociopolitical context as well as in public policies, in order to minimize the inequities and weaknesses observed in this population.